The Performative Divine: Velichappadu's Role in Challenging Marginalization in Malabar - Sunesh, P. (University of Jaffna, 2024)
In Malabar region of Kerala, India, the Velichappadu- oracle of god, is a unique socio-religious practice where individuals, primarily from marginalized communities, transform into god figures known as Velichappadu. This transformation elevates them to the status of a deity, jiggling sharp ceremonial sword, vermilion outfit, aramani (waistlet) and chilanka (anklet),the sprayings of turmeric powder, and dances to the beat of the chenda while speaking with believers as deities. Velichappadu is religiously attached with the Kodungallur Bhagavathi temple, Trissur Kerala, and believes to have connection with the myth of Kannagi. The study explores the velichappadu's evolution from artist to deity and examines how it is acting as a tool for social change by erasing the lines of marginalization. By analyzing historical contexts, ritualistic practices, and community perceptions, this study aims to uncover how the Velichappadu tradition serves as a mechanism for challenging social norms, empowering marginalized groups, and fostering communal solidarity in the region of Malabar. Through Ethnography and other qualitative research methods, including participant observation and interviews, the study sets the stage for a comprehensive exploration of the Velichappadu phenomenon and its broader implications for social transformation in contemporary Kerala.
Keywords: Velichappadu; Arts of marginalized; Social change; Castes in Kerala